Crystal structure of 2-bromo-11-(((fluoromethyl)sulfonyl)methyl)-6-methyl-6,11-dihydrodibenzo[c,f][1,2]thiazepine 5,5-dioxide, C16H13BrFNO4S2 - Wu Wenhui; Xiao Kun; Wang Ji; Guo Qingchun; Gao Xiaoping; Qiu Yaxian (Zeitschrift für Kristallographie - New Crystal Structures)
C16H13BrFNO4S2, monoclinic, P21/c (no. 14), a = 9.1629(2) Å, b = 17.9824(4) Å, c = 10.3488(2) Å, β = 95.501(1)°, V = 1697.33(6) Å3, Z = 4, Rgt(F) = 0.0331, wRref(F2) = 0.0804, T = 150 K.